2016
DOI: 10.1038/srep38697
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amyloid A3 Gene Expression in Adipocytes is an Indicator of the Interaction with Macrophages

Abstract: The infiltration of macrophages into adipose tissue and their interaction with adipocytes are essential for the chronic low-grade inflammation of obese adipose tissue. In this study, we identified the serum amyloid A3 (Saa3) gene as a key adipocyte-derived factor that is affected by interaction with macrophages. We showed that the Saa3 promoter in adipocytes actually responds to activated macrophages in a co-culture system. Decreasing C/EBPβ abundance in 3T3-L1 adipocytes or point mutation of C/EBPβ elements s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 55 publications
0
28
0
1
Order By: Relevance
“…Therefore, further studies need to be done to reveal possible implications of other adipokines in such regulation. Especially, the role of adipokines that are reported to be involved in immune response (eg, adipsin, acylation stimulation protein [ASP], serum amyloid A3 [SAA3], and IL‐17D), should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies need to be done to reveal possible implications of other adipokines in such regulation. Especially, the role of adipokines that are reported to be involved in immune response (eg, adipsin, acylation stimulation protein [ASP], serum amyloid A3 [SAA3], and IL‐17D), should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous reports, we isolated total RNAs from db / db and db /+ epididymal adipose tissues and compared the gene expression profiles by DNA microarray data analysis (Sanada et al., , ). Data analysis indicated that 1810 transcript levels were significantly up‐regulated in the adipose tissue of db / db mice ( p < .05).…”
Section: Resultsmentioning
confidence: 99%
“…DNA microarray analysis was performed in accordance with our previous study (Sanada et al., , ). Total RNA derived from epididymal fat of AREG and control mice at 8 weeks of age was isolated using RNeasy Lipid Tissue Mini Kit and subjected to cRNA synthesis for a DNA microarray analysis according to the manufacturer's instructions (whole mouse genome 60‐mer oligo microarray, Agilent Technologies, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies of viral infections in humans [ 5 , 8 , 9 ], including COVID-19 [ 10 ], suggest that SAA is a sensitive biomarker for early diagnostics and treatment and a predictor of the viral disease outcome. Mouse model studies report that SAA3 is a sensitive biomarker of excessive inflammation upon vaccination [ 11 ] and of macrophage infiltration of the adipose tissue in obesity [ 12 ]. Whether SAA is not just a marker but also an active participant in disease is intensely investigated, and numerous, sometimes conflicting, functions have been ascribed to this mysterious protein.…”
Section: Introductionmentioning
confidence: 99%